ANALISIS PELUANG HEMAT ENERGI LISTRIK GEDUNG JURUSAN TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI UNIVERSITAS GADJAH MADA - , AKHMAD FAIZAL KHABIBI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Electrical energy consumption in Indonesia has increased each year along with the increase of the population, the increase of economics society, and the rapid development of technology. Based on PLN statistical data, electric sales in 2012 rose up to 173% compared to the sales in 2004. PLN electrical energy supply which still dominated by fossil fuels shows that electrical energy produced by PLN is still limited, so the savings in its utilization needs to be done. A variety of ways can be done in the energy savings, in PP No. 30 2007 the Government formulate the steps to deal with the energy crisis in Indonesia through energy conservation. One of the steps in the energy conservation is energy audit. An energy audit is an evaluation and identification of energy saving opportunities as well as the recommendations in improving energy efficiency . Energy-saving opportunities research in JTETI UGM building was conducted to find out electric power consumption, electricity condition, and the energy-saving opportunities that can be done in JTETI UGM building. Research carried out by collecting primary data and secondary data through observation, interviews and measurements. This research shows that electrical power consumption of JTETI UGM building can be categorized as very wasteful, with IKE 357,413 kWh/m2/year. Electrical energy-saving opportunities in JTETI UGM building can be done by raising the occupants awareness , replacing the electrical load components with a more efficient components and reducing load power operational time . About 11.346,2446 kWh energy saving opportunities every month can be achieved with the investment of 163.093.300 ,- IDR with payback period in 16 months.